(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The main objective of the paper is to demonstrate the presence of Easter Island´s history in Neruda´s writing, mainly in The separate Rose (1972). I propose that in order to read these poems it is necessary to connect them with historic events and characters, because through those connections new readings –until now absent from nerudian criticism– may be born.